The effect of lemon on the essential element concentrations of herbal and fruit teas - Gorgulu, T. Y.; Ozdemir, O. D.; Kipcak, A. S.; Piskin, M. B.; Derun, E. M. (SPRINGER SINGAPORE PTE LTD, 2016)
In this study, the effect of lemon addition to the element content of several herbal and fruit teas is investigated. Lemon addition to tea is a traditional cultural practice in many countries. For this purpose, fennel, mint, and sage are selected as herbal teas, and apple, lemon, and rosehip are selected as fruit teas. The essential elements of calcium, cobalt, copper, iron, potassium, magnesium, sodium, phosphorus, selenium, and zinc are determined in the aforementioned teas with and without lemon addition by using an inductively coupled plasma optical emission spectrometer. From the results of the experiments, the lemon addition caused different changes with respect to the tea type. Potassium (1178 ppm) in apple tea with lemon, sodium (215.1 ppm) in fennel tea with lemon, and calcium (81.88 ppm) and magnesium (53.83 ppm) in mint tea with lemon are found to be the four major essential elements in the teas. In general, the elemental contents are increased with the lemon addition for all of the tea types, except for Na in the sage tea.
Keywords: Herbal tea; Fruit tea; Essential elements; Lemon effect; SALVIA-OFFICINALIS L.; VITAMIN-C CONTENT; TRACE-ELEMENTS; MULTIELEMENT ANALYSIS; MEDICINAL HERBS; BIOAVAILABILITY; STABILITY; INFUSIONS; BEVERAGES; EXTRACTS; Food Science & Technology